THE PLAY MOTOR ACTIVITY IN THE PRIMARY SCHOOL - IMPLEMENTATION AND PROBLEMS - V. Ivanova (Trakia Journal of Sciences)
PURPOSE: The research is provoked by the problems that accompany the implementation of play activities in the forms of motor training in primary school. METHODS: A survey is conducted among teachers teaching the subject "Physical Education and Sports" in I - IV grade. RESULTS: The analysis of the answers of the respondents reveals negatives that hinder the effective pedagogical process. CONCLUSIONS: The following problems are pointed out as the most significant: the insufficient number or technical malfunction of the sports equipment, tools, equipment; limited working space - both outdoors and indoors; the lack of clear guidelines and specific guidelines for planning and implementation of educational content in physical education, including games, especially - sports; unclear criteria and standards for assessing the success and progress of students in the game activities; the lack of guidelines for working with students with special educational needs or health problems; insufficient proposed forms, such as seminars, training courses, etc. to acquaint the primary teachers with novelties in the educational process in Physical Education and Sport.